ANALISIS KOMPARASI DAMPAK PEMBANGUNAN DESA DALAM PENGENTASAN MASALAH PENGANGGURAN - Oki Oktaviana; Iman Rifai (Jurnal Kebijakan Pembangunan Daerah, 2023)
The high unemployment rate is an indicator of one of the development problems in Banten province. Different with the national condition, unemployment in rural areas in Banten province is relatively always higher than in urban areas. Therefore, this study aims to analyze the unemployment problem in the rural areas of Banten province as a measure of the effectiveness of village development that has been carried out. This research is a descriptive quantitative study based on a comparative analysis of unemployment data in rural and urban areas in Banten province before and after the enactment of Law No. 6/2014 on Villages. The results showed that the downward trend of unemployment in rural areas in Banten province in the 2010-2014 period was faster than that in the 2015-2019 period. This shows that the implementation of village development after Law 6/2014 has not been able to create an acceleration of unemployment alleviation in rural areas. The lack of optimization of village development in terms of reducing unemployment is due to the lack of alignment of budgeting in the field of community development and community empowerment. Village development budgeting that has been carried out is more concentrated in the fields of village development implementation and village government administration